On Sacrificing and Self-Preservation: One Interpretation - Jovanović, Đokica R. (Collection of Papers of the Faculty of Philosophy in Priština, 2014)
One of the initial points of departure is actually an idea by Branko Lazarević, an almost forgotten writer and critic, who stated that „sacrifice and the only pure self-denial“, adding that we are witness to two types of sacrifice: „Bearing a cross signifies to a victim that one still remains on the other (non-spiritual, author’s note) side“. Sacrificing therefore means that one has entered this (spiritual, author’s note) side. In this paper the author is discussing the phenomenon of the so-called transparent, visible sacrifice, i.e. those sacrifices that are on “this side”, which, as such, is the only one detectable in sociological investigations. The basic premise of the paper claims that the basis of the phenomenon of sacrifice there is a need for co-participation, submissiveness towerds authority (be it military, religious, political…) which is a condition for coexistence in a community. Survival is possible only as an extension of physical existence or as a participating part of a commemorative culture. The paper also analyses the assumption that the culture of sacrifice, among other things, constitutes itself under a set of possible punitive measures (physical or moral). Among others, some ideas by Russian authors stating that the institution of a sacrifice develops in a state of fear caused by ritual murder of a state’s subjects, smerds, before the dead body of their supreme leader. The Russian writers naturally do not rule out a practice of ritual killing of subjects in different and older cultures other than that of Proto-Slavic ones.
Keywords: remembrance; smerds; culture; sacrifice